Association of tumor burden with the eligibility of upfront intensification therapy in metastatic castration‐sensitive prostate cancer: A multicenter retrospective study. (16th May 2020) - Hatakeyama, Shingo; Narita, Shintaro; Takahashi, Masahiro; Sakurai, Toshihiko; Kawamura, Sadafumi; Hoshi, Senji; Ishida, Masanori; Kawaguchi, Toshiaki; Ishidoya, Shigeto; Shimoda, Jiro; Sato, Hiromi; Hamano, Itsuto; et al.
Abstract : Objectives: To evaluate the association of tumor burden with the prognosis in real‐world patients with metastatic castration‐sensitive prostate cancer and to investigate the eligibility for upfront intensification therapy. Methods: We retrospectively evaluated 679 patients with metastatic castration‐sensitive prostate cancer who were initially treated with conventional androgen deprivation therapy between August 2001 and November 2018. The primary purpose was to investigate the eligibility for upfront intensification therapy based on the progression of metastatic castration‐resistant prostate cancer. The secondary purpose included the comparison of the metastatic castration‐resistant prostate cancer progression rate, metastatic castration‐resistant prostate cancer‐free survival and overall survival after castration‐resistance in CHAARTED low‐ or high‐volume disease patients. Results: The number of patients with metastatic castration‐resistant prostate cancer progression was 119 (52%) and 319 (71%) in the low‐ and high‐volume disease groups, respectively. The metastatic castration‐resistant prostate cancer progression rate ( P < 0.001) and castration‐resistant prostate cancer‐free survival ( P < 0.001) were significantly different between the low‐ and high‐volume disease groups, but no difference was found for overall survival after castration resistance ( P = 0.363). Multivariate Cox regression analysis showed no significant association between tumor burden and overall survival after castration resistance ( P = 0.522; hazard ratio 1.14). Conclusions: The progression rate in metastatic castration‐resistant prostate cancer patients with the low‐volume disease under conventional androgen deprivation therapy is approximately 50%. Upfront intensification therapy might be beneficial for approximately half of patients with low‐volume disease. A novel maker to predict the castration‐resistant status is required to select optimal patients for upfront intensification therapy.